Political Economy of Agricultural Distortions : The Literature to Date - Swinnen, Johan F. M. (World Bank, Washington, DC, 2017)
The 1980s and first half of the 1990s were a very active period in the field of political economy of agricultural protection. While the past decade has witnessed a slowdown in this area, there have been very important developments on political economy in other parts of the economics profession. This paper reviews key new insights and developments in the general political economy literature and draws implications for the study of the political economy of distortions to agricultural incentives.